Evaluation of oxidant stress in Wilson’s disease and non-Wilsonian chronic liver disease in childhood - Buket DALGIÇ,; Nesrin SÖNMEZ,; Gürsel BİBEROĞLU,; Alev HASANOĞLU,; Deniz ERBAŞ, (Turkish Journal of Gastroenterology, 2019)
-